Peculiarities of the menstrual cycle in girls living in the Murmansk region - E. I. Grigorieva; A. A. Martynova (Acta Biomedica Scientifica, 2024)
The aim of the study. To assess the characteristics of the menstrual cycle and ovulation disorders in girls aged 15–17 years.Materials and methods. The study was carried out in 2022–2023 in the Murmansk region in Apatity. A total of 225 girls with average age of 16.5 ± 0.03 years took part in the study. The characteristics of the menstrual cycle and ovulation disorders were studied according to the guidelines of the International Federation of Gynecology and Obstetrics.Results of the study. In the study group, the onset of menarche (13.1 years) is observed at a later age compared to the girls living in other regions of Russia and neighboring countries (12.6–12.9 years). Every seventh girl has an irregular menstrual cycle, every fifth girl has a cycle duration of more than 38 days. Heavy menstruation occurs in every third girl, intermenstrual uterine bleeding – in every thirteenth girl. Half of the girls have painful periods (dysmenorrhea). Among ovulation disorders, the most common is abnormal uterine bleeding – 34.7 %. Also, intermenstrual uterine bleeding (8.0 %), primary amenorrhea (2.7 %) and polycystic ovary syndrome (1.3 %) are registered. Among gynecological pathology, in addition to ovulation disorders, we registered vulvovaginal candidiasis and paraurethral cyst.Conclusion. The analysis of the obtained results showed that only 20.4 % of girls do not have gynecological pathology, which to a certain extent indicates a low level of reproductive health of girls. Asaresult, it is necessary to diagnose and treat diseases which can cause the development of ovulation disorders more carefully and at earlier stages of sexual development. The work was carried out as part of the research topic No. FMEZ-2022-0012.